2015
DOI: 10.1080/01694243.2015.1049325
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of pulsed laser ablation on shear strength and mode I fracture toughness of Al/epoxy adhesive joints

Abstract: The present work describes an experimental study about the shear strength and the mode I fracture toughness of adhesive joints with substrates pre-treated by pulsed laser ablation. An ytterbium-doped pulsed fiber laser was employed to perform laser irradiation on AA6082-T4 alloy. Morphological and chemical modifications were evaluated by means of surface profilometry, scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). Thick adherend shear tests were carried out in order to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The disordered surface structures were proposed to be responsible for enhanced mechanical interlocking of the adhesive and the metal surface resulting in an increased SLS strength before and after aging and e.g. DCB-and T-peel strength of aluminum epoxy joints [22,23,49].…”
Section: Results In Context With Previous Studies Of Laser-pretreated...mentioning
confidence: 99%
“…The disordered surface structures were proposed to be responsible for enhanced mechanical interlocking of the adhesive and the metal surface resulting in an increased SLS strength before and after aging and e.g. DCB-and T-peel strength of aluminum epoxy joints [22,23,49].…”
Section: Results In Context With Previous Studies Of Laser-pretreated...mentioning
confidence: 99%
“…Finally, we emphasize that our results reiterate the need to integrate proper surface pre-treatments within the car body manufacturing. From this standpoint, previous works by the authors carried out on aluminum and titanium alloys 30,31 already indicated that pulsed laser irradiation might be an interesting potential candidate to the purpose. Indeed, current lasers are provided with high-precision beam positioning systems, which ensure the ability to treat the target surfaces selectively, and with fairly accurate geometrical control.…”
Section: T-jointsmentioning
confidence: 97%
“…Their study proved that fiber lasers are considerably promising in the field of material processing. [ 152 ] Hagiwara et al. investigated the use of fiber lasers with a high peak power for processing biomedical materials.…”
Section: Application Prospectsmentioning
confidence: 99%
“…Their study proved that fiber lasers are considerably promising in the field of material processing. [152] Hagiwara et al investigated the use of fiber lasers with a high peak power for processing biomedical materials. First, they used a hollow fiber to generate double pulses of 200 and 300 fs to improve the peak power of the pulses.…”
Section: Materials Processingmentioning
confidence: 99%